Enhanced Functional Coupling of Hippocampal Sub-regions in Congenitally and Late Blind Subjects - Ma, Guangyang; Yang, Dan; Qin, Wen; Liu, Yong; Jiang, Tianzi; Yu, Chunshui (Frontiers in Neuroscience, 2017)
The hippocampus has exhibited navigation-related changes in volume and activity after visual deprivation; however, the resting-state functional connectivity (rsFC) changes of the hippocampus in the blind remains unknown. In this study, we focused on sub-region-specific rsFC changes of the hippocampus and their association with the onset age of blindness. The rsFC patterns of the hippocampal sub-regions (head, body and tail) were compared among 20 congenitally blind (CB), 42 late blind (LB), and 50 sighted controls (SC). Compared with the SC, both the CB and the LB showed increased hippocampal rsFCs with the posterior cingulate cortex, angular gyrus, parieto-occpital sulcus, middle occipito-temporal conjunction, inferior temporal gyrus, orbital frontal cortex, and middle frontal gyrus. In the blind subjects, the hippocampal tail had more extensive rsFC changes than the anterior hippocampus (body and head). The CB and the LB had similar changes in hippocampal rsFC. These altered rsFCs of the hippocampal sub-regions were neither correlated with onset age in the LB nor the duration of blindness in CB or LB subjects. The increased coupling of the hippocampal intrinsic functional network may reflect enhanced loading of the hippocampal-related networks for non-visual memory processing. Furthermore, the similar changes of hippocampal rsFCs between the CB and the LB suggests an experience-dependent rather than a developmental-dependent plasticity of the hippocampal intrinsic functional network.